Genetic polymorphisms and arterial stiffness - Zhou, Sixiang (Trinity College (Dublin, Ireland). School of Medicine. Discipline of Pharmacology & Therapeutics, 2008)
Arterial stiffness exerts a major influence on cardiac afterload and coronary perfusion. Indices of arterial stiffness have therefore been proposed as surrogate markers of cardiovascular risk and as potential therapeutic targets. Aging, genetic and environmental factors together lead to structural and functional changes of the arterial wall, which may result in decreased elasticity and increased stiffness. The process of vascular stiffening has been proven to be closely associated with ageing. Whilst the genetic contributions to arterial stiffness are far from clear, the current view is that this is a polygenetic process which may also be influenced by pathological and environmental factors. The aim of this thesis was to determine if some specific genes contribute to arterial stiffening. Blood samples from the untreated hypertensive patients were collected and genetic DNA of these samples was extracted. Polymorphisms of candidate genes including the collagen III gene, the elastin gene, the matrix metalloproteinases (MMP-9) gene, the adiponectin gene, the receptor of advanced glycation end products (RAGE) gene and the G-protein beta 3-subunit gene were studied using restriction fragment length polymorphism (RFLP) methods. MMP-9 and plasma adiponectin levels were also measured in blood samples from untreated hypertensive subjects. Aortic stiffness was measured by pulse wave velocity (PWV), and augmentation index (AIx) was measured by applanation tonometry to estimate wave reflection.
Keywords: Pharmacology, Ph.D.; Ph.D. Trinity College Dublin